2014
DOI: 10.1097/eja.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

Self-positioning followed by induction of anaesthesia and insertion of a laryngeal mask airway versus endotracheal intubation and subsequent positioning for spinal surgery in the prone position

Abstract: www.clinicaltrials.gov identifier: NCT01041352.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…Three pro-con debate reports were also excluded. A total of 12 articles [8][9][10][11][12][13][14][15][16][17][18][19] were deemed eligible for inclusion in the present review ( Figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three pro-con debate reports were also excluded. A total of 12 articles [8][9][10][11][12][13][14][15][16][17][18][19] were deemed eligible for inclusion in the present review ( Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…The remaining 10 articles [10][11][12][13][14][15][16][17][18][19] pertained to the elective use of second-generation SADs in patients in the prone position (Table 1). One study reported the successful use of PLMA by experienced users (not trainee anesthesiologists) in 245 patients in the prone position [10].…”
Section: Journal Of Anesthesia and Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published randomized-controlled trial comparing induction in the supine position (with endotracheal intubation) vs in the prone position (with insertion of a supraglottic airway [SGA]), the only benefit found was a statistically, albeit not clinically, significant reduction in time to readiness for commencement of surgery (25 min vs 30 min, respectively; P \ 0.001). 12 Potential loss of the airway, limited choices in airway devices and airway maneuvres, and adverse hemodynamics are the major deterrents to the induction of anesthesia in the awake prone patient. 13 On the other hand, patients with an unstable spine may be at risk of further neurological injury while anesthetized during prone positioning.…”
Section: Induction / Airway Managementmentioning
confidence: 99%
“…Dans une étude randomisée contrôlée publiée récemment qui comparait l'induction en décubitus dorsal (avec intubation endotrachéale) à une induction en position ventrale (avec insertion d'un dispositif supraglottique), le seul avantage observé était une réduction significative, d'un point de vue statistique mais non clinique, du temps jusqu'à ce que le patient soit prêt pour le début de la chirurgie (25 min vs 30 min, respectivement; P \ 0,001). 12 La perte potentielle des voies aériennes, les choix limités en matière de dispositifs et de manoeuvres de prise en charge des voies aériennes, ainsi que les complications hémodynamiques potentielles, sont les points majeurs de dissuasion quand il s'agit d'induire une anesthésie générale en position ventrale. 13 Par contre, les patients dont la colonne vertébrale est instable courent le risque d'une lésion neurologique supplémentaire s'ils sont inconscients pendant le retournement en position ventrale.…”
Section: Induction / Prise En Charge Des Voies Aériennesunclassified